Konstruksi Sosial Media Pada Makna Realitas TikTok di Masyarakat - Kussanti, Devy Putri (Jurnal Public Relations (J-PR), 2022)
More and more social media users, especially TikTok, create a new social construction about giving meaning to content creators. The TikTok application which has video, photo and music editing features can be used by users to create content that has its own purpose from the content creator or TikTok user. Reality is a social construction that is actually created by the individual/society. Through TikTok, individuals/communities can easily express themselves and give meaning to the content they are creating. This study uses a descriptive qualitative research method with a social constructivism point of view. So it was found that TikTok's social media construction became a reason to understand how an incident was reconstructed by TikTok to be conveyed to netizens.